Pengaruh Temperatur Pengovenan terhadap Sifat Mekanik Komposit Hibrid Polyester Berpenguat Serat Glass dan Serat Daun Gewang - Adoniram Sabuin; Kristomus Boimau; Dominggus G. H. Adoe (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2015)
Abstract The purpose of this study was to determine the effect of temperature on mechanical properties oven hybrid composite glass fiber and polyester fiber reinforce gewang leaves the fiber volume fraction (Vf) of 32%. Materials used in this study is polyester resin, glass fiber and fiber gewang leaves. Tensile test specimens were made according to ASTM standard D638 while bending test specimens made according to ASTM standard D790. The test specimen by hand lay-up method followed by suppression and left for one day. Furthermore, the composite standard tensile and bending test, then the test specimen treated with different heating. Tensile test results showed that the heat-treated specimens 1000C for one hour has a tensile strength greater than others, amounting to 62.264 MPa, while the lowest tensile strength of 28.805 MPa obtained on specimens that are subjected to 2000C for three hours. Bending test results also showed that the heat-treated specimens 1000C for one hour to have the largest bending strength which is equal to 112.340 MPa, while the lowest bending strength of 57.714 MPa obtained on specimens with heat treatment for 2000C for three hours. The results of the macro picture shows cracks in bending test specimens, whereas the tensile test specimens seen the fiber pullout, debonding and brittle fracture.